An Analysis of Grammatical Error on Simple Sentences by Third Semester Students at Mathematic Study Program in Batanghari University Academic Year 2019 - Alda Nadia. M; Yanti Ismiyati (Universitas Batanghari Jambi, 2020)
The purpose of this research is to analysis the grammatical errors in simple sentences by Third Semester students at Mathematic Study Program in Batanghari University academic year 2019/2020. The method of this research is descriptive qualitative. The samples of this research are thirteen mathematic study program students at third semester in Batanghari University. The instruments of the research are test and interview. Based on the result, students often made grammatical errors in their test, the errors were classified into three categories; addition, omission, and misformation. Then researcher calculated the total errors made by them using the formula in order to find out the most common grammatical error. It is found that the most grammatical error made by them is Misformation which is up to 77,04%, and the smallest percentage of errors made by students is Addition which is 1,64%. Besides, the researcher also conducted a short interview to confirm the data on the test. Based on the finding above, the researcher concludes that mathematic study program students at third semester need to study grammar deeper in order to avoid misunderstanding in writing simple sentences.Key Words: Error Analysis, Grammar, Simple Sentence.